Malakoplakia of the gastrointestinal tract: clinicopathologic analysis of 23 cases - Michael Lee; Huaibin Mabel Ko; Anthony Rubino; Hwajeong Lee; Ryan Gill; Stephen M. Lagana (BMC, 2020)
Abstract Background Malakoplakia is an uncommon, tumor-like inflammatory disease characterized by impaired histiocytes that are unable to completely digest phagocytized bacteria. The genitourinary tract is the most common site of involvement, however, cases have also been described in the gastrointestinal tract, suggesting that it is the second most common site of involvement. This study investigates the clinical and histologic features of malakoplakia in the gastrointestinal tract. Case presentation For 23 gastrointestinal specimens (biopsies and resections) from patients with a pathologic diagnosis of malakoplakia, we recorded the gender, age, location, primary diagnosis, endoscopic or surgical indication, endoscopic/gross impression and immune status (immunocompromised vs. immunocompetent). Conclusion Malakoplakia occurred throughout the length of the gastrointestinal tract with most of the cases located in the sigmoid colon and rectum (n = 10); other sites included the transverse and descending colon (n = 4), stomach/gastroesophageal junction (n = 4), appendix (n = 2), cecum (n = 1), small bowel (n = 1), and the peri-anal area (n = 1). Endoscopically, these lesions most commonly appeared as polyps (n = 10) or masses (n = 5), other clinical endoscopic impressions varied from a thickened area/fibrosis to mucosal erythema. Most patients were immunocompromised due to a disease state (e.g. organ transplantation, cancer diagnosis, autoimmune condition) and/or medication effect. Eight patients with malakoplakia were on immunosuppressive medications (8/23, 35%). Common immunosuppressed disease states included cancer (n = 9), autoimmune disease (n = 5), status post organ transplantation (n = 4), diabetes (n = 5), infection/sepsis (n = 3), and HIV/AIDS (n = 1). Some patients had multiple co-morbidities (i.e. diabetes and organ transplant). Twenty-one patients with malakoplakia were in an immunosuppressive state (21/23, 91%).